Formation Control of Multiple Agents with Preserving Connectivity and its Application to Gradient Climbing - Do, Khac (Agora University Editing House-- CCC Publications, R & D Agora, 2012)
A design of cooperative controllers that force a group of N mobile agents with limited communication ranges to perform a desired formation is presented. The proposed formation control system also preserves initial communication connectivity and guarantees no collisions between the agents. The formation control design is based on smooth step functions, potential functions, and the Lyapunov direct method. The proposed formation control system is applied to solve a gradient climbing problem where the gradient average of a distributed field is estimated over a bounded region using the field measurement by the agents.